Alcohol Consumption and Visual Impairment in a Rural Northern Chinese Population. (December 2014) - Li, Zhijian; Xu, Keke; Wu, Shubin; Sun, Ying; Song, Zhen; Jin, Di; Liu, Ping
Abstract Purpose: To investigate alcohol drinking status and the association between drinking patterns and visual impairment in an adult population in northern China. Methods: Cluster sampling was used to select samples. The protocol consisted of an interview, pilot study, visual acuity (VA) testing and a clinical examination. Visual impairment was defined as presenting VA worse than 20/60 in any eye. Drinking patterns included drinking quantity (standard drinks per week) and frequency (drinking days in the past week) Results: Information on alcohol consumption was obtained from 8445 subjects, 963 (11.4%) of whom reported consuming alcohol. In multivariate analysis, alcohol consumption was significantly associated with older age (p < 0.001), male sex (p < 0.001), and higher education level (p < 0.01). Heavy intake (>14 drinks/week) was associated with higher odds of visual impairment. However, moderate intake (>1–14 drinks/week) was significantly associated with lower odds (adjusted odds ratio, OR, 0.7, 95% confidence interval, CI, 0.5–1.0) of visual impairment (p = 0.03). Higher drinking frequency was significantly associated with higher odds of visual impairment. Multivariate analysis showed that older age, male sex, and higher education level were associated with visual impairment among current drinkers. Age- and sex-adjusted ORs for the association of cataract and alcohol intake showed that higher alcohol consumption was not significantly associated with an increased prevalence of cataract (OR 1.2, 95% CI 0.4–3.6), whereas light and moderate alcohol consumption appeared to reduce incidence of cataract. Conclusion: Drinking patterns were associated with visual impairment. Heavy intake had negative effects on distance vision; meanwhile, moderate intake had a positive effect on distance vision.